Pediatric emergency medicine fellowship point‐of‐care ultrasound training in 2020. Issue 4 (17th September 2021) - Cramer, Natan; Cantwell, Lauren; Ong, Hilary; Sivasankar, Shyam M.; Graff, Danielle; Lawson, Simone L.; Wilson, Paria M.; Noorbakhsh, Kathleen A.; Mickley, Megan; Zuckerbraun, Noel S.; Sobolewski, Brad; Soung, Jane K.; et al.
Abstract: Objectives: The primary objective was to survey pediatric emergency medicine (PEM) leaders and fellows regarding point‐of‐care ultrasound (POCUS) training in PEM fellowship programs, including teaching methods, training requirements, and applications taught. Secondary objectives were to compare fellows' and program leaders' perceptions of fellow POCUS competency and training barriers. Methods: This was a cross‐sectional survey of U.S. PEM fellows and fellowship program leaders of the 78 fellowship programs using two online group‐specific surveys exploring five domains: program demographics; training strategies and requirements; perceived competency; barriers, strengths, and weaknesses of POCUS training; and POCUS satisfaction. Results: Eighty‐three percent (65/78) of programs and 53% (298/558) of fellows responded. All participating PEM fellowship programs included POCUS training in their curriculum. Among the 65 programs, 97% of programs and 92% of programs utilized didactics and supervised scanning shifts as educational techniques, respectively. Sixty percent of programs integrated numerical benchmarks and 49% of programs incorporated real‐time, hands‐on demonstration as training requirements. Of the 19 POCUS applications deemed in the literature as core requirements for fellows, at least 75% of the 298 fellows reported training in 13 of those applications. Although less than half of fellows endorsed competency for identifying intussusception, ultrasound‐guided pericardiocentesis, and transvaginal pregnancy evaluation, a higher proportion of leaders reported fellows as competent for these applications (40% vs. 68%, p ≤ 0.001; 21% vs. 39%, p = 0.003; and 21% vs. 43%, p ≤ 0.001). Forty‐six percent of fellows endorsed a lack of PEM POCUS evidence as a training barrier compared to 31% of leaders (p = 0.02), and 39% of leaders endorsed a lack of local financial support as a training barrier compared to 23% of fellows (p = 0.01). Conclusions: Although most PEM fellowship programs provide POCUS training, there is variation in content and requirements. Training does conform to many of the expert recommended guidelines; however, there are some discrepancies and perceived barriers to POCUS training remain.